JUBAH DAN KOTEKA: DUALISME BUDAYA DALAM RELIGIOSITAS ORANG PAPUA PEGUNUNGAN - Yohanes Kayame (STP Reinha Larantuka, 2023)
This article aims to discuss clothing, namely the robe and the Koteka in the religious expressions of the Papuan people, especially in the mountainous regions. The robe as a representation of western or Middle Eastern culture, the Romans, Greeks, which exist in the Catholic religious tradition. On the other hand, the Koteka is the traditional clothing for men of the Papuan people of the mountains. But these two objects can be used on one occasion, for example in the Eucharistic Celebration which is considered a big and important celebration. Also during the usual Eucharistic celebrations in the Church. The robes are worn by religious and laity as liturgical officers, while the koteka is worn by lay people who also participate in the Eucharistic Celebration. On the one hand, it displays the uniqueness of the local culture, on the other hand, it shows the richness of the church in inculturation. The methodology in this writing uses qualitative methods, by examining previous books and journals according to the topics discussed. The data obtained were analyzed using a descriptive phenomenological approach. Writing does not make a comparative study between the koteka and the robe, but a phenomenological study of religious culture. In this writing it is found that robes and koteka are two garments from different cultures. But both of them have a very holy and noble value in the celebration of the Eucharist and in everyday life. So that koteka is not something that is primitive and underdeveloped but has a sacred meaning